Protection of Human Rights in the Framework of Global Judicial Reforms - Gariaga, Oleg; Marchenko, Olena; Kuchynska, Iryna; Rieznikova, Viktoriia; Patsuriia, Nino (Fakultas Syariah UINSI Samarinda, 2025)
The purpose of the article is to analyse the relationship between judicial reforms and human rights protection, especially in the light of global and international changes. The article examines how judicial reforms carried out in different countries, aimed at improving the efficiency, accessibility, and fairness of the judicial process, affect the exercise and protection of fundamental human rights and freedoms. The authors examine the case studies of Colombia and Turkey in the context of their judicial reforms to understand whether reforms are always sufficient to ensure human rights. Based on the study, it is established that reforms alone are not enough. Sustained political will and international influence are also needed. It is established that the protection of human rights in the context of global judicial reforms is a relevant and significant topic that requires attention and improvement in the modern world. Protection of human rights through judicial reforms only meets the needs of modern society.